Dính rồi ! [Ça mord !] Ancrages sociaux et recompositions territoriales de la pêche de loisirs à Hồ Chí Minh Ville (Việt Nam) - Emmanuelle Peyvel; Ngọc Thắng Dương; Cẩm Thi Trần (EchoGéo)
This article examines recreational fishing in Hồ Chí Minh City, Vietnam's largest metropolitan area. Whether casual or sportive, we show that this practice remains the prerogative of working and middle class males, thereby exposing their territoriality within the city, ranging from opportunistic fishing in the city center to fee-based fishing in dedicated locations on the outskirts (câu cá giải trí and khu du lịch sinh thái). Beyond the catch itself, fishing involves a negotiated access to nature, calmness and freshness, that are increasingly coveted with the commodification of leisure, urbanization and the growing regulation of public spaces, threatening the most precarious.